2017
DOI: 10.1002/pro.3366
|View full text |Cite
|
Sign up to set email alerts
|

Computational predictions of cysteine cathepsin‐mediated fibrinogen proteolysis

Abstract: Fibrin clot formation is a proteolytic cascade of events with thrombin and plasmin identified as the main proteases cleaving fibrinogen precursor, and the fibrin polymer, respectively. Other proteases may be involved directly in fibrin(ogen) cleavage, clot formation, and resolution, or in the degradation of fibrin-based scaffolds emerging as useful tools for tissue engineered constructs. Here, cysteine cathepsins are investigated for their putative ability to hydrolyze fibrinogen, since they are potent proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Cathepsin partial or complete fibrinolysis may prevent full solid clots from forming or staying in a protective way during thrombin-mediated clot formation. However, our recent study also shows that cathepsins potentially can be involved in fibrin formation as they can hydrolyze fibrinogen as well [19]. This putative conflict will need to be resolved to understand the participation of this additional class of proteases in hemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin partial or complete fibrinolysis may prevent full solid clots from forming or staying in a protective way during thrombin-mediated clot formation. However, our recent study also shows that cathepsins potentially can be involved in fibrin formation as they can hydrolyze fibrinogen as well [19]. This putative conflict will need to be resolved to understand the participation of this additional class of proteases in hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has used molecular docking and bioinformatics sequence specificity analysis (PACMANS), to predict potential binding and cleavage sites of cathepsins K, L and S on fibrin [19]. It was determined that catK, L, and S are capable of binding to the α, β, and γ chains on fibrinogen at overlapping and different sites.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of pre-adipocyte cells, cleavage of fibronectin by cathepsin S was suggested as a possible mechanism for their differentiation [173]. Recent in silico and in vitro studies reported that cathepsins K, L, and S could cleave fibrinogen and fibrin, resulting in fragments that differ from the ones produced by plasmin, which opened the door to further investigate their roles in vascular homeostasis, especially in coagulation-associated diseases [174,175]. Moreover, cathepsin K was recently demonstrated to have an essential role in skeletal muscle remodeling, dysfunction, and fibrosis following injury [176].…”
Section: Ecm Proteolysis and The Cathepsinsmentioning
confidence: 99%
“…Our previous characterization of engineered skeletal muscle tissues demonstrated the activity of proteolytic enzymes (such as myotube-secreted catL) that can degrade the fibrin-based ECM and thus lead to diminished mechanical integrity and functionality over time. 24 Along with recently described modeling, 46 we underscore catL as an alternative fibrin(ogen)lytic protease. In this study, we show preliminary evidence that secreted cathepsin had fibrinogenolytic activity (Fig.…”
Section: Discussionmentioning
confidence: 52%